Globally Important Agricultural Heritage Systems (GIAHS) of China: the challenge of complexity in research. Issue 2 (27th April 2015) - Fuller, Anthony M.; Min, Qingwen; Jiao, Wenjun; Bai, Yanying
Abstract : The challenge of researching Globally Important Agricultural Heritage Systems (GIAHS) as complex systems forms the subject matter of this study. Complex adaptive systems are those that combine natural ecological processes with human interactions to produce a mutually supportive agro‐ecological system. In China, these highly varied systems have the added dimension of long historical time, in that they have evolved over many centuries and thus add a historical dimension to the natural and human dimensions of complexity. In preparing research on GIAHS, it is clear that seeing GIAHS sites as whole systems is an essential starting and ending point. Examining the adaptive capacity of a GIAHS with its multiple scales and complex interdependencies is a major challenge for researchers accustomed to specialized disciplinary thinking. A GIAHS represents a mature agro‐ecological system with human agency as a central component that has been honed over many centuries, and has already adapted to many perturbations and changes. The beauty of the GIAHS is in the integration of custom, knowledge, and practice, and it should be studied for its "wholeness" as well as for its resilience and capacity for "self organization." The agro‐ecological approach opens the possibility of researching a system as a whole and of taking its complexity seriously. This study reviews the essential features of the GIAHS as a complex adaptive system where uncertainty is normal and surprise is welcome and, in a case study of Qingtian rice–fish culture system, focuses on new perturbations, namely loss of young people and the introduction of tourism.